The level of ambition and its relationship to performing the skill of serving from above With Volleyball for female students - Abboud, Prof. Dr. Haider Mahmoud; Kadhim, Prof. Dr. Rawaa Alawi (Sulaimani Journal for Humanities, 2025)
The scientific Progress that the world is witnessing at the present time is one of the basic reasons foe the progress of human life in its various fields , including the sports field . thes progress can only be achieved through diligent scientific studies based on several sciences that are interconnected and linked to the practice of sports , and among these sciences that contribute significantly to the development of Sports of all Kinds and for all sports groups that practice them is sports psychology . After serving from above , it is a form of powerful serving skill , which is similar in technical performance to the smash hit skill in terms of the curvature of the torso and the hand meeting the ball from above . lt is oreferable that this form of skill is always learned before starting to learn the smash hit . there is little interest in the psychological aspect of the concept of the level of ambition among college students in general and female students in general and female students in particular , and this is supported by there level of performance in sports , especially in football . The plane and its various skills , specifically the skill of serving from above . Therefore , the two researchers decided to study the relationship between the level of ambition of the female students and their performance in the overhead serve skill in volleyball .
Keywords: Level of ambition; serving; volleyball